Inhibitory Activities of Daidzein Derivatives Against Human Vascular Smooth Muscle Cells Proliferation and Migration - Zhao, Wen-Hong; Hu, Jiang-Ning; Peng, You; Li, Jing; Fan, Ya-Wei; Li, Yu; Liu, Rong; Deng, Ze-Yuan (Asian Journal of Chemistry, 2011)
In order to explore the application possibility of daidzein derivatives (DDs), 3-(4'- phenylsulphonylphenyl)-7-phenylsulphonyl-4H-chromen-4-one (DD1) and 3-(4'- hydroxyphenyl)-7-phenylsulphonyl-4H-chromen-4-one (DD2), their absorption inhibitory activities against human vascular smooth muscle cells (VSMCs) proliferation and migration were investigated in present study. Results showed that the partition coefficients of DD1 and DD2 were much better than that of daidzein in octanol-water solvent. Final absorptions of DD1, DD2 and daidzein by human umbilical vascular smooth muscle cells were 71.67, 61.44 and 54.58 %, respectively. The inhibitory rate of DD1, DD2 and daidzein of 100 μM measured against vascular smooth muscle cells proliferation were 84.47, 68.53 and 66.35 %, respectively. Human umbilical vascular smooth muscle cells migration ability was dose-dependently inhibited by daidzein derivatives and daidzein. At the concentration of 100 μM, the inhibitory effect of migrated cell number which cells were treated with DD1, DD2 and daidzein were respectively at 85.00, 73.75 and 67.50 % compared with untreated control. Meanwhile, the cell migration distance of them were significantly inhibited as 81.17, 71.43 and 63.64 % of untreated control, respectively (p < 0.05). All those results from the experiment suggested that these derivatives of daidzein as functional food ingredients might contribute to the prevention of cardiovascular diseases via inhibiting vascular smooth muscle cells proliferation and migration.